Inclusive Education-Perception of Parents of Students with Special Needs in Segregated Settings in Dubai - GANESH, SEEMA (2017)
Inclusion and inclusive education is the order of the day. The government is trying its best to make UAE an inclusive society by coming up with laws and many other supporting developments. A large number of students with special needs study in private and government schools and rehabilitation centers. This study investigates the views and attitudes of parents of students studying in segregated settings in Dubai. It has been conducted on the parents of 3 well known special need centers in Dubai. The study has been done in order to take into account the perception of these parents about inclusive education and to look for best practices so that more students with special needs can be included in the main stream setting. The data required for the research was collected through both quantitative and qualitative means. The methods used were survey and semi structured interview. Triangulation method was used to increase the validity and reliability of the study. The study found that overall parents were in favour of the idea of inclusion but they had many concerns about their kids attending mainstream schools. Most of the concerns were regarding the lack of trained teachers and resources in these schools as compared to special needs schools.